Identification of NTRK fusions in pediatric mesenchymal tumors. Issue 8 (18th January 2017) - Pavlick, Dean; Schrock, Alexa B.; Malicki, Denise; Stephens, Philip J.; Kuo, Dennis J.; Ahn, Hyunah; Turpin, Brian; Allen, Justin M.; Rosenzweig, Mark; Badizadegan, Kamran; Ross, Jeffrey S.; Miller, Vincent A.; et al.
Abstract: Background: NTRK fusions are known oncogenic drivers and have recently been effectively targeted by investigational agents in adults. We sought to assess the frequency of NTRK fusions in a large series of pediatric and adolescent patients with advanced cancers. Procedure: Genomic profiles from 2, 031 advanced cancers from patients less than 21 years old who were assayed with comprehensive genomic profiling were reviewed to identify NTRK fusions. Results: Total of nine cases (0.44%) harbored NTRK fusions, including novel partners. Four of these cases were in children less than 2 years old for which infantile fibrosarcoma was considered as a diagnosis, and two harbored the canonical ETV6 ‐ NTRK3 . The remaining cases carried other diagnoses, at least one that carried the diagnosis of inflammatory myofibroblastic tumor. Conclusions: NTRK fusions occur in a subset of young patients with mesenchymal or sarcoma‐like tumors at a low frequency, and are eminently druggable targets via either investigational agents or approved drugs.